The Moderating Role of Sharia Compliance in the Relationship between Sustainability Reporting Disclosure and Firm Value: : Evidence from Mining and Energy Companies Listed on the Indonesia Stock Exchange. - Azwar Anwar; Nur Alim Bahri; Febrina Nur Ramadhani; Andi Asti Handayani (Economics and Digital Business Review, 2026)
This study examines the effect of sustainability reporting on firm value with Sharia compliance as a moderating variable in mining and energy companies listed on the Indonesia Stock Exchange (IDX). The research is grounded in Stakeholder Theory and Sustainability Theory, which emphasize that companies are responsible not only to shareholders but also to broader stakeholders, including society and the environment. Sustainability disclosure is expected to improve transparency and strengthen stakeholder trust, which may ultimately influence firm value. However, previous studies show inconsistent findings, suggesting that the relationship may depend on certain moderating factors. This study employs a quantitative approach using multiple regression analysis with EViews. Sustainability reporting is measured using the Global Reporting Initiative (GRI) index, firm value is measured using Tobin’s Q, and Sharia compliance acts as the moderating variable. Leverage (DER) and profitability (ROA) are included as control variables. The sample consists of 63 observations from 21 mining and energy companies during the period 2022–2024. The results indicate that sustainability reporting does not have a significant effect on firm value, even when moderated by Sharia compliance. Prior to moderation, sustainability reporting shows a negative effect on firm value, while after moderation only profitability (ROA) has a significant influence. These findings suggest that sustainability disclosure alone may not be sufficient to increase firm value in the mining and energy sector.